2012
DOI: 10.5114/aoms.2012.28600
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between changes in selected thrombotic and inflammatory factors, echocardiographic parameters and the incidence of venous thrombosis after pacemaker implantation based on our own observations

Abstract: IntroductionThrombosis (VTh) is a rare dangerous complication of pacemaker implantation (PM). The aim of the study was to determine the dynamics of change in selected thrombotic and inflammatory factors after PM.Material and methodsThe study involved 81 patients (30 female, mean age: 71.1 years) with PM, divided into two groups. Group A (71 patients) consisted of patients without VTh, whereas group B (10 patients) comprised the patients with VTh. A transthoracic echocardiogram (TTE) and a venous ultrasound (VU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
2
11
0
2
Order By: Relevance
“…The expressive rate of the study endpoints confirmed the observation of clinical practice that these problems are frequent after intravascular manipulation of patients with CIED and allowed the search for risk factors 9‐11,19 . Among the variables that were associated with the occurrence of UEDVT, two were independent predictors: the collateral circulation present in preoperative venography, which increased by 4.7 times the chance of this outcome and the transvenous lead extraction, which increased 27 times this risk.…”
Section: Discussionsupporting
confidence: 65%
“…The expressive rate of the study endpoints confirmed the observation of clinical practice that these problems are frequent after intravascular manipulation of patients with CIED and allowed the search for risk factors 9‐11,19 . Among the variables that were associated with the occurrence of UEDVT, two were independent predictors: the collateral circulation present in preoperative venography, which increased by 4.7 times the chance of this outcome and the transvenous lead extraction, which increased 27 times this risk.…”
Section: Discussionsupporting
confidence: 65%
“…PAI-1 also plays an active role in this process 1 . In the present study, although the caval clots were not spontaneously formed, we found evidence that similar biochemical markers may play role in the process of propagation 33 34 .…”
Section: Discussionsupporting
confidence: 42%
“…These risk factors included pacemakers19, splenectomy20, non-0 blood type21, lupus anticoagulant22, thyroid replacement therapy/subacute hypothyroidism23, malignancy24 and age10.…”
Section: Discussionmentioning
confidence: 99%